Antibacterial nanocellulose hydrogel as well as preparation method and application thereof

By introducing a combined formula of antibacterial nanocellulose hydrogels into medical hydrogels, the shortcomings of existing hydrogels in bactericidal and strength properties are solved, and more efficient antibacterial effects and more stable structural performance are achieved.

CN119798712APending Publication Date: 2025-04-11ANHUI SNOW DRAGON FIBER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411863092.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing medical hydrogels have shortcomings in sterilization and strength properties, which cannot meet the needs of medical rescue, and are prone to pulling deformation and tearing during use.

Method used

An antibacterial nanocellulose hydrogel is used, which consists of nanocellulose, polylactic acid, hydroxymethyl chitosan, tannic acid, antibacterial agent and strengthening agent. The antibacterial agent is prepared by a combination of zinc acetate powder, polyaminolytic acid and DMADDM to form a three-layer encapsulation structure; the reinforcement is silanized by MTMS and nanocellulose to enhance the mechanical properties of the hydrogel.

Benefits of technology

It significantly improves the antibacterial and strength properties of the hydrogel, can effectively inhibit bacterial growth, maintain stability during use, and reduce pulling deformation and tearing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses antibacterial nanocellulose hydrogel as well as a preparation method and application thereof, and relates to the technical field of hydrogel, the antibacterial nanocellulose hydrogel comprises the following components in parts by weight: 50-60 parts of nanocellulose, 5-10 parts of polylactic acid, 10-15 parts of hydroxymethyl chitosan, 5-10 parts of tannic acid, 10-15 parts of an antibacterial agent and 10-15 parts of an enhancer; wherein the antibacterial agent is prepared from the following raw materials: zinc acetate powder, poly (lysine) ammonia and dodecyl dimethylamine methacrylate in a mass ratio of 20: (1-3): (100-120); an antibacterial agent in the antibacterial nanocellulose hydrogel is of a three-layer wrapping structure, all layers of materials can achieve a synergistic effect, and the layer-by-layer wrapping structure is beneficial to slow release of antibacterial components and enhancement of the antibacterial ability; the antibacterial agent and the enhancer can be combined with each other, so that the strength performance of the hydrogel can be improved; and due to the hydroxymethyl chitosan and the tannic acid, the hydrogel has good biocompatibility, so that the hydrogel can play a better role when being applied to wound dressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to an antibacterial nanocellulose hydrogel and a preparation method and application thereof. Background Art

[0002] The skin is the largest organ in the human body and is a basic barrier that protects the internal tissues of the human body, maintains fluid balance, and prevents the invasion of pathogens. However, the skin is easily damaged by acute trauma, chronic ulcers, and diseases, leading to excessive loss of protein and water, bacterial infection, and even immune system disorders. When the wound is deep into the dermis or subcutaneous tissue, the spontaneous healing process of the wound is difficult. At the same time, bacterial infection also poses a serious threat to wound healing, which can delay collagen synthesis and prolong wound healing time.

[0003] Traditional wound dressings such as gauze, bandages, band-aids, sponge pads, etc. are dry dressings that can absorb wound exudate, but they are easy to adhere to the injured area and are difficult to remove. When the dressing is replaced again, it will damage the new granulation tissue and cause secondary injury. In recent years, a large number of studies have shown that compared with a dry environment, a moist environment can promote wound healing faster, reduce the risk of infection, and reduce pain. Based on this, bactericidal hydrogels have been developed for wound dressings.

[0004] Hydrogel is a soft material with a three-dimensional network structure formed by physical or chemical cross-linking of polymers. It can absorb a large amount of water and swell but is insoluble in water. It is a type of polymer material that combines water absorption and water retention. Hydrogel used as wound dressing can maintain a moist environment for the wound, promote cell growth and reduce inflammation, which is beneficial to wound healing.

[0005] However, although existing medical hydrogels can provide a good repair environment for wounds, their bactericidal properties are still low and cannot meet the needs of medical rescue. Moreover, due to their special soft material structure, their strength performance is highly limited and they are prone to pulling, deformation and tearing during use, affecting patients' use. Summary of the invention

[0006] The purpose of the present invention is to provide an antibacterial nanocellulose hydrogel and a preparation method and application thereof, to solve the following technical problems:

[0007] How to improve the antibacterial and strength properties of nanocellulose hydrogels.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] In a first aspect, the present invention discloses an antibacterial nanocellulose hydrogel, comprising the following components in parts by weight: 50-60 parts of nanocellulose, 5-10 parts of polylactic acid (PLA), 10-15 parts of hydroxymethyl chitosan, 5-10 parts of tannic acid, 10-15 parts of an antibacterial agent, and 10-15 parts of a reinforcing agent; wherein the raw materials for preparing the antibacterial agent include zinc acetate powder, polylysine and dodecyl dimethylamine methacrylate (DMADDM) in a mass ratio of 20:(1-3):(100-120);

[0010] Preferably, nanocellulose is 55 parts, PLA is 8 parts, hydroxymethyl chitosan is 12 parts, tannic acid is 8 parts, antibacterial agent is 12 parts, and enhancer is 12 parts;

[0011] Preferably, the mass ratio of zinc acetate powder, poly(l-lysine) and DMADDM in the antibacterial agent is 10:1:55.

[0012] Furthermore, the preparation method of the antibacterial agent is carried out according to the following steps:

[0013] Step A, dissolving zinc acetate powder in a stirring tank filled with deionized water, the amount ratio of zinc acetate to deionized water is 1g:15mL; then adding sodium hydroxide dropwise to adjust the pH to 10, stirring evenly at 60°C, then adding polylysine, stirring and reacting at 150°C for 10h, polylysine contains a large number of amino groups, which can interact with divalent zinc ions in zinc acetate, so that the divalent zinc ions are evenly distributed in the polylysine amino body and preferentially nucleate; the obtained reactant is washed with ethanol and deionized water for 3 times respectively, and then transferred to a vacuum drying oven and dried at 120°C for 6h to obtain core-shell encapsulated modified nano zinc oxide particles, and at the same time, due to the interaction between zinc ions and hydrogen bonds between the inner core molecules of polylysine amino molecules, the growth can be delayed and the particle size can be reduced;

[0014] Step B, dissolving the modified nano zinc oxide particles in a stirring tank filled with anhydrous ethanol, the amount ratio of the modified nano zinc oxide particles to the anhydrous ethanol is 1g:20mL; sodium hydroxide is added dropwise to the stirring tank to adjust the pH to 10, and then DMADDM is added and stirred for 12 hours. The carboxylate group in DMADDM is deprotonated in an alkaline environment and has a negative charge, and the amino group on the polylysine molecular chain in the modified nano zinc oxide particles has a positive charge. The two are combined with each other under the action of electrostatics, so that DMADDM is wrapped around the outside of the polylysine in the modified nano zinc oxide particles to form a three-layer structure; the obtained reactant is washed three times with ethanol and deionized water respectively, and then transferred to a vacuum drying oven, dried at 120°C for 6 hours, and then transferred to a grinder for grinding and refining to obtain an antibacterial agent.

[0015] Furthermore, the preparation method of the enhancer is carried out according to the following steps:

[0016] Step M, dissolving methyltrimethoxysilane (MTMS) in a stirring tank filled with ethanol, the amount ratio of MTMS to ethanol being 1 g:10 mL, stirring at 50° C. for 30 min, then dropping acetic acid to adjust the pH to 3, to obtain a mixed solution;

[0017] Step N, slowly add the mixed solution into distilled water at 60-80°C, while stirring and keeping warm, and stop stirring after 5-7 hours. During this process, the methoxy groups in MTMS are converted into hydroxyl groups. Let stand for 24 hours to obtain a hydrolyzate with a precipitate at the bottom;

[0018] Step L: filtering and separating the hydrolyzate, transferring the obtained filter material to an oven and drying it at 120° C. for 5-6 hours, and then transferring it to a grinder for grinding and refining to obtain a strengthener.

[0019] In a second aspect, the present invention further discloses a method for preparing the antibacterial nanocellulose hydrogel as described above, which is carried out in sequence according to the following steps:

[0020] S1. Add nanocellulose and anhydrous ethanol into a ball mill for ball milling. The amount ratio of nanocellulose to anhydrous ethanol is 1 g: 5 mL, and the ball-to-material ratio is 20: 1. PLA is added in small amounts and multiple times during the grinding process to grind together. The nanocellulose and PLA are fully mixed to improve their dispersion performance. After the grinding is completed, the material is dried to obtain a mixed material. The mixed material is dissolved in a magnetic stirrer filled with deionized water, and magnetically stirred at 40° C. for 24 hours to obtain a double mixed liquid with a solid content of 25%;

[0021] S2, adding hydroxymethyl chitosan and tannic acid to the double mixed solution, stirring and mixing for 15 minutes, then adding the antibacterial agent and the enhancer, stirring and reacting at 80° C. for 3-4 hours to obtain a hydrogel pre-liquid;

[0022] S3. Spread the hydrogel precursor onto a substrate, such as a glass plate, with a thickness of 0.5-2 mm, let it stand for 24 hours to solidify, and then peel it off from the substrate to obtain a hydrogel.

[0023] Tannic acid reacts with nanocellulose and hydroxymethyl chitosan through non-covalent bonds, which can improve the mechanical properties of the hydrogel on the one hand, and the antibacterial and antioxidant capabilities of the hydrogel on the other hand. The outermost DMADDM in the antibacterial agent combines with the hydroxyl group converted from the methoxy group in MTMS through the methacryloyl group. At the same time, MTMS also undergoes a silanization reaction with nanocellulose, causing the fiber molecular chains of nanocellulose to become entangled in space, making the fibers closer together and the structure more stable, thereby improving the mechanical properties of the hydrogel.

[0024] In a third aspect, the present invention further discloses an application of the antibacterial nanocellulose hydrogel as described above for wound dressing.

[0025] Beneficial effects of the present invention:

[0026] 1. In the antibacterial nanocellulose hydrogel of the present invention, the antibacterial agent is a three-layer packaging structure, the innermost layer is zinc oxide particles formed by oxidation of zinc acetate, the zinc oxide particles are wrapped with poly(l-lysine)amide, and the poly(l-lysine)amide is wrapped with DMADDM. All three have excellent antibacterial properties and can achieve a synergistic effect. The layer-by-layer packaging structure is conducive to the sustained release of antibacterial components and enhances the antibacterial ability.

[0027] 2. In the antibacterial nanocellulose hydrogel of the present invention, the antibacterial agent and the reinforcing agent can be combined with each other. Specifically, the outermost DMADDM in the antibacterial agent is combined with the hydroxyl group converted from the methoxy group in MTMS through the methacryloyl group. At the same time, MTMS also undergoes a silanization reaction with the nanocellulose, so that the fiber molecular chains of the nanocellulose are entangled in space, the fibers are closer together, and the structure is more stable, thereby improving the strength performance of the hydrogel.

[0028] 3. Hydroxymethyl chitosan and tannic acid are added to the antibacterial nanocellulose hydrogel of the present invention, so that it has good biocompatibility. At the same time, tannic acid acts with nanocellulose and hydroxymethyl chitosan through non-covalent bonds, which can improve the mechanical properties of the hydrogel on the one hand, and on the other hand, it can also improve the antibacterial and antioxidant capabilities of the hydrogel, so that it can play a better role when used in wound dressings. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0031] Preparation Example 1

[0032] Preparation of antimicrobial agent:

[0033] Step A, dissolving 10g of zinc acetate powder in a stirring tank filled with 150mL of deionized water, then dropping sodium hydroxide to adjust the pH to 10, stirring evenly at 60°C, then adding 1g of polylysine, stirring and reacting at 150°C for 10h, washing the obtained reactant with ethanol and deionized water for 3 times respectively, then transferring to a vacuum drying oven, and drying at 120°C for 6h to obtain 10.92g of core-shell encapsulated modified nano zinc oxide particles;

[0034] Step B, dissolving the modified nano zinc oxide particles in a stirring tank containing 218.4 mL of anhydrous ethanol, adding sodium hydroxide dropwise to the stirring tank to adjust the pH to 10, then adding 55 g of DMADDM and stirring the reaction for 12 h, washing the obtained reactant with ethanol and deionized water for 3 times, then transferring it to a vacuum drying oven, drying it at 120 ° C for 6 h, and then transferring it to a grinder for grinding to obtain an antibacterial agent.

[0035] Preparation Comparative Example 1

[0036] Preparation of antimicrobial agent:

[0037] Compared with Preparation Example 1, the only difference is that step B is not performed, and the modified nano zinc oxide particles prepared in step A are directly used as an antibacterial agent.

[0038] Preparation Comparative Example 2

[0039] Compared with Preparation Example 1, the only difference is that polylysate is not added in step A, and the other steps and conditions are exactly the same, and the antibacterial agent is finally prepared.

[0040] Preparation Example 2

[0041] Preparation of the fortifier:

[0042] Step M, dissolving 50 g of MTMS in a stirring tank containing 500 mL of ethanol, stirring at 50° C. for 30 min, then dropping acetic acid to adjust the pH to 3 to obtain a mixed solution;

[0043] Step N, slowly add the mixed solution into distilled water at 60-80° C., while stirring at the same time, stirring for 5-7 hours, stop, and let stand for 24 hours to obtain a hydrolyzate with a precipitate at the bottom;

[0044] Step L: filtering and separating the hydrolyzate, transferring the obtained filter material to an oven and drying it at 120° C. for 5.5 h, and then transferring it to a grinder for grinding to obtain a strengthener.

[0045] Example 1

[0046] Preparation of antibacterial nanocellulose hydrogel:

[0047] The first step is to add 55g of nanocellulose and 275mL of anhydrous ethanol into a ball mill for ball milling, with a ball-to-material ratio of 20:1. During the grinding process, PLA is added in 4 times and ground together, with 2g added each time. After the grinding is completed, the material is dried to obtain a mixture, and the mixture is dissolved in a magnetic stirrer filled with 252mL of deionized water, and magnetically stirred at 40°C for 24h to obtain a double mixed liquid with a solid content of 25%;

[0048] Step 2: Add 12 g of hydroxymethyl chitosan and 8 g of tannic acid to the double mixed solution, stir and mix for 15 min, then add 12 g of the antibacterial agent prepared in Preparation Example 1 and 12 g of the enhancer prepared in Preparation Example 2, stir and react at 80° C. for 3.5 h to obtain a hydrogel pre-liquid;

[0049] The third step is to spread the hydrogel precursor liquid on a glass plate with a thickness of 1 mm, let it stand for 24 hours to solidify, and then peel it off from the substrate to obtain a sheet of hydrogel.

[0050] Example 2

[0051] The first step is to add 50g of nanocellulose and 250mL of anhydrous ethanol into a ball mill for ball milling, with a ball-to-material ratio of 20:1. During the grinding process, PLA is added twice and ground together, with 2.5g added each time. After the grinding is completed, the material is dried to obtain a mixture, and the mixture is dissolved in a magnetic stirrer filled with 220mL of deionized water, and magnetically stirred at 40°C for 24h to obtain a double mixed liquid with a solid content of 25%;

[0052] Step 2: Add 10 g of hydroxymethyl chitosan and 5 g of tannic acid to the double mixed solution, stir and mix for 15 min, then add 10 g of the antibacterial agent prepared in Preparation Example 1 and 10 g of the enhancer prepared in Preparation Example 2, stir and react at 80° C. for 3 h to obtain a hydrogel pre-liquid;

[0053] The third step is to spread the hydrogel precursor liquid on a glass plate with a thickness of 1 mm, let it stand for 24 hours to solidify, and then peel it off from the substrate to obtain a sheet of hydrogel.

[0054] Example 3

[0055] The first step is to add 60g of nanocellulose and 300mL of anhydrous ethanol into a ball mill for ball milling, with a ball-to-material ratio of 20:1. During the grinding process, PLA is added in 5 times and ground together, with 2g added each time. After the grinding is completed, the material is dried to obtain a mixture, and the mixture is dissolved in a magnetic stirrer filled with 280mL of deionized water, and magnetically stirred at 40°C for 24h to obtain a double mixed liquid with a solid content of 25%;

[0056] Step 2: Add 15 g of hydroxymethyl chitosan and 10 g of tannic acid to the double mixed solution, stir and mix for 15 min, then add 15 g of the antibacterial agent prepared in Preparation Example 1 and 15 g of the enhancer prepared in Preparation Example 2, stir and react at 80° C. for 4 h to obtain a hydrogel pre-liquid;

[0057] The third step is to spread the hydrogel precursor liquid on a glass plate with a thickness of 1 mm, let it stand for 24 hours to solidify, and then peel it off from the substrate to obtain a sheet of hydrogel.

[0058] Comparative Example 1

[0059] Compared with Example 1, the only difference is that the antibacterial agent prepared in Preparation Example 1 is replaced by the antibacterial agent prepared in Comparative Preparation Example 1, and the other conditions and steps are exactly the same, and finally a hydrogel is prepared.

[0060] Comparative Example 2

[0061] Compared with Example 1, the only difference is that the antibacterial agent prepared in Preparation Example 1 is replaced by the antibacterial agent prepared in Comparative Preparation Example 2, and the other conditions and steps are exactly the same, and finally a hydrogel is prepared.

[0062] Comparative Example 3

[0063] Compared with Example 1, the only difference is that the reinforcing agent prepared in Preparation Example 2 is replaced by MTMS, and the other conditions and steps are exactly the same, and finally a hydrogel is prepared.

[0064] Next, the antibacterial performance of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the testing method was as follows:

[0065] Gram-negative Escherichia coli (E.co li) and Gram-positive Staphylococcus aureus (S.aureus) were selected to test the antibacterial properties of the samples. 100 μL of bacterial solution with a concentration of 106 CFU / mL was applied to the LB plate, and the prepared hydrogel was cut into a disc with a diameter of 5 mm, and then pasted on the LB plate. After culturing in a 37°C incubator for 24h, 48h and 72h, the size of the inhibition zone was observed and recorded, and the results were listed in Table 1-2. Table 1-2 is as follows:

[0066] Table 1 Antibacterial activity of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 against E.coli

[0067]

[0068] Table 2 Antibacterial activity of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 against S. aureus

[0069]

[0070] By analyzing the data in Table 1-2, it can be seen that the hydrogel prepared in Example 1-3 has a significantly larger inhibition zone within 24h, 48h and 72h than that in Comparative Example 1-2, and the inhibition zone is slightly larger than that in Comparative Example 3, which indicates that adding polylysine and DMADDM to the antibacterial agent can enhance the antibacterial properties of the hydrogel.

[0071] Next, the strength performance of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the test methods included tensile test, compression test and shear test, and the final test results were listed in Table 3, which is as follows:

[0072] Table 3 Strength properties of hydrogels prepared in Examples 1-3 and Comparative Examples 1-3

[0073]

[0074] By analyzing the data in Table 3, it can be seen that the hydrogels prepared in Examples 1-3 have significantly higher strength test results than those in Comparative Examples 1-3, which indicates that the antibacterial nanocellulose hydrogel of the present invention has higher strength performance.

[0075] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. An antibacterial nanocellulose hydrogel, characterized in that: The invention comprises the following components in parts by weight: 50-60 parts of nanocellulose, 5-10 parts of polylactic acid, 10-15 parts of hydroxymethyl chitosan, 5-10 parts of tannic acid, 10-15 parts of antibacterial agent and 10-15 parts of reinforcing agent; wherein the raw materials for preparing the antibacterial agent comprise zinc acetate powder, polylysine amino and dodecyl dimethylamine methacrylate in a mass ratio of 20:(1-3):(100-120).

2. The antibacterial nanocellulose hydrogel according to claim 1, characterized in that The preparation method of the antibacterial agent is carried out according to the following steps: Step A, dissolving zinc acetate powder in deionized water, adding sodium hydroxide dropwise to adjust the pH to 10, stirring evenly at 60° C., then adding polylysine, stirring and reacting at 150° C. for 10 hours, washing and drying the obtained reactant to obtain core-shell encapsulated modified nano zinc oxide particles; Step B, dissolving the modified nano zinc oxide particles in anhydrous ethanol, adding sodium hydroxide dropwise to adjust the pH to 10, then adding dodecyl dimethylamine methacrylate and stirring the reaction for 12 hours, washing, drying and grinding the obtained reactant to obtain an antibacterial agent.

3. The antibacterial nanocellulose hydrogel according to claim 2, characterized in that In step A, the ratio of zinc acetate to deionized water is 1 g:15 mL.

4. The antibacterial nanocellulose hydrogel according to claim 2, characterized in that In step B, the usage ratio of the modified nano zinc oxide particles to anhydrous ethanol is 1 g:20 mL.

5. The antibacterial nanocellulose hydrogel according to claim 1, characterized in that The preparation method of the enhancer is carried out according to the following steps: Step M, dissolving methyltrimethoxysilane in ethanol, stirring at 50° C. for 30 min, then adding acetic acid dropwise to adjust the pH to 3 to obtain a mixed solution; Step N, slowly add the mixed solution into distilled water at 60-80° C., while keeping warm and stirring, stop stirring after 5-7 hours, and let it stand for 24 hours to obtain a hydrolyzate with precipitation at the bottom; Step L, filtering and separating the hydrolyzate, transferring the obtained filter material to an oven for drying, and grinding after drying to obtain a strengthener.

6. The antibacterial nanocellulose hydrogel according to claim 5, characterized in that In step M, the usage ratio of methyltrimethoxysilane to ethanol is 1 g:10 mL.

7. The antibacterial nanocellulose hydrogel according to claim 5, characterized in that In step L, the obtained filter material is transferred to an oven for drying at the following parameters: drying temperature 120° C., drying time 5-6 h.

8. A method for preparing the antibacterial nanocellulose hydrogel according to any one of claims 1 to 7, characterized in that: Follow the steps below: S1. Add nanocellulose and anhydrous ethanol into a ball mill for grinding. During the grinding process, add polylactic acid in small amounts and multiple times for grinding. After the grinding is completed, dry the mixture to obtain a mixed material. Dissolve the mixed material in deionized water and stir it magnetically at 40° C. for 24 hours to obtain a double mixed liquid. S2, adding hydroxymethyl chitosan and tannic acid to the double mixed solution, stirring and mixing for 15 minutes, then adding the antibacterial agent and the enhancer, stirring and reacting at 80° C. for 3-4 hours to obtain a hydrogel pre-liquid; S3. Spread the hydrogel pre-liquid on the substrate with a thickness of 0.5-2 mm, let it stand for 24 hours to solidify, and then peel it off from the substrate to obtain a hydrogel.

9. The method for preparing the antibacterial nanocellulose hydrogel according to claim 8, characterized in that: In step S1, the solid content of the double mixed liquid is 25%.

10. An application of the antibacterial nanocellulose hydrogel according to any one of claims 1 to 7, characterized in that: For wound dressing.